1997
DOI: 10.1046/j.1365-2036.1997.00227.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of intragastric acidity in healthy subjects dosed with ranitidine 75 mg: a comparative study with cimetidine and placebo

Abstract: Background Despite the widespread use of over‐the‐counter H2‐receptor antagonists little is known about their duration of action on human gastric acid secretion. There are studies reporting inhibitory effects for up to 9 h post‐dose but few data beyond this period. Methods Profiles of 20‐h intragastric acidity were measured simultaneously in 24 healthy subjects who were dosed (at 12.30 h) with either ranitidine 75 mg, cimetidine 200 mg or placebo in a three‐way crossover study, according to a standard protocol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 5 publications
(10 reference statements)
1
12
0
Order By: Relevance
“…The onset of action of a low dose of ranitidine on gastric acidity observed in the present study agrees with a number of other reports. An over‐the‐counter dose of a histamine H 2 ‐receptor antagonist first reduced gastric acid concentration 1–2 h after dosing and this reduction persisted for several hours 15 , 28–31 , 35 …”
Section: Discussionmentioning
confidence: 99%
“…The onset of action of a low dose of ranitidine on gastric acidity observed in the present study agrees with a number of other reports. An over‐the‐counter dose of a histamine H 2 ‐receptor antagonist first reduced gastric acid concentration 1–2 h after dosing and this reduction persisted for several hours 15 , 28–31 , 35 …”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies have, however, demonstrated that at over‐the‐counter doses, cimetidine has a slightly lower antisecretory efficacy than famotidine and ranitidine 9 , . 11 On the other hand, a new effervescent preparation of 200 mg cimetidine has been shown to induce a more rapid suppressive effect on intragastric acidity than film‐coated tablets of famotidine 31 . This is likely to induce a more rapid symptom relief during the daytime.…”
Section: Discussionmentioning
confidence: 99%
“…Studies comparing the efficacy of the H 2 ‐antagonists at over‐the‐counter dosage were usually performed either in fasting or postprandial subjects 6 –11 . It is well known that meal intake reduces the acid inhibitory effect of high dose H 2 ‐antagonists 12 –14 .…”
Section: Introductionmentioning
confidence: 99%
“…PPIs show stronger and longer acid suppression than H 2 -RAs [31][32][33][34][35]. Acid suppression lasts up to 24 h with PPIs versus 3 and 15 h with antacids and H 2 -RAs, respectively [36][37][38]. PPIs have an early onset of action (acid suppression approximately 1.5 h after administration; comparable with H 2 -RAs) that manifests clinically within 1-3 days [31,[39][40][41][42][43][44][45].…”
Section: Benefits Of An Otc-ppi Treatment Compared With Current/ Prevmentioning
confidence: 99%